2009
DOI: 10.1080/09583150903243870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of several commercial biocontrol products on European and North American populations ofPhytophthora ramorum

Abstract: Five commercially available biological control products were tested in vitro with seven isolates of Phytophthora ramorum from North American (NA1, NA2), and European (EU1) populations. The in vitro tests included dual culture methods and detached leaf assays on wounded Rhododendron and Camellia leaves. Variability in response to biocontrol agents among isolates of P. ramorum from North American and European populations was examined. In dual culture tests, both Bacillus subtilis products (Companion † and Serena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
1
37
1
Order By: Relevance
“…A study by Elliott et al (2009a) on the biocontrol options for P. ramorum reports that control of P. ramorum on Rhododendron foliage with BCAs was comparable to the one obtained with some contact fungicides, although it was lower than with systemic fungicides tested in the study by Wagner and colleagues, which was cited in the RAPRA report. Nevertheless, Elliott et al (2009a) point out that with fungicides there is an issue of resistance development, as well of course as environmental and toxicity considerations.…”
Section: Options To Reduce Infestation and Magnitude Of Impact In Thementioning
confidence: 97%
See 3 more Smart Citations
“…A study by Elliott et al (2009a) on the biocontrol options for P. ramorum reports that control of P. ramorum on Rhododendron foliage with BCAs was comparable to the one obtained with some contact fungicides, although it was lower than with systemic fungicides tested in the study by Wagner and colleagues, which was cited in the RAPRA report. Nevertheless, Elliott et al (2009a) point out that with fungicides there is an issue of resistance development, as well of course as environmental and toxicity considerations.…”
Section: Options To Reduce Infestation and Magnitude Of Impact In Thementioning
confidence: 97%
“…On this point, it is interesting that the majority of Belgian P. ramorum isolates have become resistant to metalaxyl One problem in adopting BCAs as a control strategy for P. ramorum may be that there was great variability among P. ramorum isolates in their response to the commercial Biocontrol Agents (BCAs) tested (Elliott et al, 2009a). However, there is certainly some potential as all treatments reduced P. ramorum lesion size on both Rhododendron and Camellia (Elliott et al, 2009a).…”
Section: Options To Reduce Infestation and Magnitude Of Impact In Thementioning
confidence: 99%
See 2 more Smart Citations
“…In Canada only fosetyl-Al (Aliette † ; Bayer CropScience Inc., Canada) was registered for control of P. ramorum at the time of this study. Elliott et al (2009) conducted in vitro tests (dual culture and detached-leaf assays) using commercially-prepared biological control products. They found that biofungicides containing Trichoderma spp.…”
mentioning
confidence: 99%